Faktor-faktor yang Berhubungan dengan Kecelakaan Kerja pada Operator Dump Truck di Bagian Produksi di Perusahaan Tambang Batubara - Nugroho, Subagyo Amin; Akbar, Sulung Alfianto; Rahmatullah, Ilham (Faletehan Health Journal, 2024)
A "Civil Work & Mining" company in Indonesia recorded 19 cases of work accidents in 2022 and 17 cases in 2023 in the production department. In 2023, 13 incidents involved dump truck operations causing property damage, of which 73% of incidents were caused by unsafe behavior and 27% by unsafe conditions. Although the number of work accidents had decreased, the company had not reached zero incidents. The purpose of this study was to find out the factors that contribute to work accidents among dump truck operators. This study used a cross-sectional design. A total of 92 dump truck operators were selected by purposive sampling and surveyed through an online questionnaire that had been tested for its validity. The data was tested using a chi-square test with a 95% confidence level. The results of the analysis showed a significant relationship between work accidents and unsafe behavior (p= 0.009), work fatigue (p=0.029) and the implementation of standard operating procedures (SOP) (p=0.014). Recommendations included the development of ongoing safety training and education to increase operator awareness of the risk of unsafe behavior, to improve supervision and control of risky activities, to implement fatigue management, and to strengthen compliance with SOPs.